Nurse’s Awareness on Ethico-legal Aspects of Nursing Profession - Paudel Subedi, Krishna Kumari; Timalsina, Kalpana; Bhele, Raja Laxmi (Journal of Nepal Health Research Council, 2018)
Background: Nursing practice amicably includes practical efficacy and ethics. Now a days legal and ethical problems associated with client care are arising day by day. Therefore, nurses should have adequate understanding of basic legal concepts and issues relevant to nursing profession in order to protect the rights of the clients and the nurses.Methods: A cross sectional descriptive design was adopted for the study. 142 nurses were included by using purposive sampling technique. Data was collected with self-administered structured questionnaire. Descriptive statistics was used to reveal demographic information. Kruskal Wallis and Mann Whitney test were used to find out association of selected demographic variables and ethico legal aspects of nursing.Results: Majority of participants were belonging to 20-29 years of age. More than half nurses had complete bachelor’s degree and had less than 10 year’s experiences. Majority of participants reported that they did not encounter any legal issues in their professional life till date. Similarly, majority of participants had average level knowledge and equate level of practice. Years of experiences and education level did not affect in knowledge level and existing practice related to ethico legal aspect of nursing. There was no significant relationship between level of knowledge and existing practice.Conclusions: Nurses have average knowledge and practice on ethico legal aspects. There is positive relationship between knowledge and practice though it is not statistically significant.